Pengaruh Kompetensi Guru, Pemberian Insentif Terhadap Kinerja Guru Sekolah Dasar Kota Tomohon - Fransiska R. Korompis (Jurnal Ilmiah Wahana Pendidikan, 2022)
Descriptive analysis revealed the following matters: (1). Variable performance of primary school teachers in the city of Tomohon in either category although more than 50% are below average. (2). The variable competence of teachers in primary schools in the city of Tomohon also fall into either category and competence of less than 50% which is above average. (3). the incentives of more than 50% of teachers perceive already well along with the certification and regional performance benefits and other incentives from the school. The results of hypothesis testing showed that: (a) there is a strong and significant relationship between teacher competence with the performance of primary school teachers in the city of Tomohon. Teacher competence contributed as much as 37.8% on teacher performance. (b). there is a significant relationship between the provision of incentives to the performance of primary school teachers in the city of Tomohon, but the contribution incentive is only about 6.2% on the performance of teachers. (c). the relationship between the two variables simultaneously (competence of teachers and the provision of incentives) with the performance of primary school teachers in the city of Tomohon is very strong and significant. Contribution of 40.1% and the remaining 59.9% is influenced by other variables.